Pengaruh Corporate Social Responsibility Terhadap Nilai Dan Kinerja Perusahaan Manufaktur - Agustin Ekadjaja; Vony Vony (Ultima Accounting : Jurnal Ilmu Akuntansi, 2011)
This study aims to determine the effect of CSR Index to the value and performance of manufacturing companies listed on the Indonesia Stock Exchange (BEI), and to find out how much the ability of the variable CSR Index in explaining the variable Tobin’s Q, ROA, and ROE manufacturing companies listed on Indonesia Stock Exchange (BEI). This study uses data sampled during the 75 years from 2007 to 2009. A statistical method used to test the research hypothesis is a simple linear regression model. Therefore, before performing hypothesis testing carried out tests of classical assumptions. The results of this study prove that, CSR Index has a significant effect on Tobin’s Q and ROE with 95% confidence level. However, CSR Index has no significant influence on ROA with 95% confidence level. Key words : CSR Index, Variabel Tobin’s Q, ROA, ROE